THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS IN NON-PROFIT ORGANIZATIONS - Erwin Indriyanto; Molina; Muhammad Nur; Kumba Digdowiseiso (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Implementing Financial Accounting Standards (SAK) in non-profit organizations is crucial for establishing financial accountability, ensuring continuity, transparency, and fostering public trust in fund management and overall organizational performance. The objective of this study is to investigate the difficulties and barriers encountered when implementing Financial Accounting Standards (SAK) in non-profit organizations and propose potential remedies. This study employs the Systematic Literature Review methodology to examine the findings of relevant research. The research findings demonstrate the intricate nature of implementing SAK (Systematic Accounting Knowledge) in non-profit organizations. This includes challenges such as a scarcity of human resources, a lack of understanding about SAK, reliance on conventional financial recording methods, and difficulties in adopting internet reporting technology. Possible solutions to these challenges encompass a comprehensive strategy that entails enhancing stakeholder comprehension, cultivating human capital with the requisite accounting expertise, and optimizing the implementation of information technology. This study highlights the importance of adopting SAK as a basis for establishing trust and efficiently carrying out social and financial obligations in non-profit organizations.